Tabloidyzacja programów informacyjnych na przykładzie wrocławskich stacji telewizyjnych - Szynol, Adam (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2013)
Wrocław is the capital city of one of the few Polish regions where regional and local terrestrial television stations compete with one another. The regional broadcaster is represented by a branch of public television, while the privately-owned Telewizja Dolnoślaska, a part of the Odra network, represents the local one. Both stations provide current affairs and journalistic programs. This paper is an attempt at a comparative analysis of the main news programs of Telewizja Wrocław (Fakty) and Telewizja Dolnośląska (Informacje). The analysis particularly focuses on the proportions of hard and soft news, which the author believes may be a confirmation of the tabloidization of the media. The comparison of the content presented by the two competing stations provides certain grounds, albeit limited, due to the scope of the analysis, to assess the state of regional and local television in Poland.